Student experiences of participating in five collaborative blended learning courses in Africa and Asia: a survey. Issue 1 (1st December 2016) - Atkins, Salla; Yan, Weirong; Meragia, Elnta; Mahomed, Hassan; Rosales-Klintz, Senia; Skinner, Donald; Zwarenstein, Merrick; ,
Abstract : Background: As blended learning (BL; a combination of face-to-face and e-learning methods) becomes more commonplace, it is important to assess whether students find it useful for their studies. ARCADE HSSR and ARCADE RSDH (African Regional Capacity Development for Health Systems and Services Research; Asian Regional Capacity Development for Research on Social Determinants of Health) were unique capacity-building projects, focusing on developing BL in Africa and Asia on issues related to global health. Objective: We aimed to evaluate the student experience of participating in any of five ARCADE BL courses implemented collaboratively at institutions from Africa, Asia, and Europe. Design: A post-course student survey with 118 students was conducted. The data were collected using email or through an e-learning platform. Data were analysed with SAS, using bivariate and multiple logistic regression. We focused on the associations between various demographic and experience variables and student-reported overall perceptions of the courses. Results: In total, 82 students responded to the survey. In bivariate logistic regression, the course a student took [ p =0.0067, odds ratio (OR)=0.192; 95% confidence interval (CI): 0.058–0.633], male gender of student ( p =0.0474, OR=0.255; 95% CI: 0.066–0.985), not experiencing technical problems ( p <0.001, OR=17.286; 95% CI: 4.629–64.554), and reporting the discussion forum as adequate for student needs ( p =0.0036, OR=0.165; 95% CI: 0.049–0.555) were found to be associated with a more positive perception of BL, as measured by student rating of the overall helpfulness of the e-learning component to their studies. In contrast, perceiving the assessment as adequate was associated with a worse perception of overall usefulness. In a multiple regression, the course, experiencing no technical problems, and perceiving the discussion as adequate remained significantly associated with a more positively rated perception of the usefulness of the online component of the blended courses. Discussion: The results suggest that lack of technical problems and functioning discussion forums are of importance during BL courses focusing on global health-related topics. Through paying attention to these aspects, global health education could be provided using BL approaches to student satisfaction.